Balanced Noise-Evoked Excitation and Inhibition in Awake Mice CA3 - Wang, Ningqian; Gan, Xiong; Liu, Yun; Xiao, Zhongju (Frontiers in Physiology, 2017)
The hippocampus is known as a neuronal structure involved in learning, memory and spatial navigation using multi-sensory cues. However, the basic features of its response to acoustic stimuli without any behavioral tasks (conditioning) remains poorly studied. Here, we investigated the CA3 response to auditory stimuli using in vivo loose-patch recordings in awake and anesthetized C57 mice. Different acoustic stimuli in addition to broadband noise such as click, FM sound and pure tone were applied to test the response of CA3 in awake animals. It was found that the wakefulness of the animal is important for the recorded neurons to respond. The CA3 neurons showed a stronger response to broadband noise rather than the other type of stimuli which suggested that auditory information arrived at CA3 via broadband pathways. Finally, we investigated the excitatory and inhibitory inputs to CA3 neurons by using in vivo whole-cell voltage-clamp techniques with the membrane potential holding at -70 and 0 mV, respectively. In awake animals, the excitatory and inhibitory inputs CA3 neurons receive induced by noise are balanced by showing stable intervals and proportional changes of their latencies and peak amplitudes as a function of the stimulation intensities.